Golfers' Performance Is Improved More by Combining Foam Rolling and Dynamic Stretch to the Lead Hip Than Practice Golf Swinging - Hamada, Yuji; Akasaka, Kiyokazu; Otsudo, Takahiro; Sawada, Yutaka; Hattori, Hiroshi; Kikuchi, Yuto; Hall, Toby (Journal of strength and conditioning research, 2024)
Hamada, Y, Akasaka, K, Otsudo, T, Sawada, Y, Hattori, H, Kikuchi, Y, and Hall, T. Golfers' performance is improved more by combining foam rolling and dynamic stretch to the lead hip than practice golf swinging. J Strength Cond Res 38(7): e391-e397, 2024-Warming up is considered effective in improving performance and preventing injury. Despite this, there have been few studies investigating warm-up programs in golf and whether specific factors contribute to improved performance. The purpose of this study was to examine the immediate effects of combined foam rolling and dynamic stretch (FR + DS) to the lead hip on golf swing performance, hip range of motion (ROM), and muscle strength in amateur golfers using a randomized crossover design. The study sample comprised 22 men (mean ± SD ; age, 32.6 ± 8.5 years, body mass index (BMI), 23.4 ± 2.7 kg·m -2 ). Subjects were assigned to receive either FR + DS or repetitive golf swing practice (SW) before crossing over to the other intervention for another day. Measurements included golf swing performance (ball speed, club head speed, flight distance ["carry"], spin rate, and launch angle), hip internal rotation (IR), and external rotation (ER) ROM, as well as hip IR and ER muscle strength. Comparisons between groups were made before and after each intervention. For golf swing performance, FR + DS improved "carry" significantly more than SW ( p < 0.05). No significant differences in golf swing performance other than "carry" were found. In addition, IR ROM and IR muscle strength of the lead hip were significantly increased in the FR + DS group ( p < 0.05). FR + DS has effects on improving lead hip IR ROM and IR muscle strength, which may facilitate golfers' swing and "carry." FR + DS shows promise as a warm-up method for amateur golfers who want to improve golf performance.